Towards the preservation of functional dependency in XML data transformation. (4th October 2010) - Shahriar, Md. Sumon; Liu, Jixue
With the advent of XML as a data representation and exchange format over the web, a massive amount of data is being stored in XML. As the use of XML grows rapidly, the task of data transformation for integration purposes in XML is getting much importance to the research community. In XML data transformation, a source schema and its conforming data are transformed to a target schema and its conforming data respectively. The source schema often has integrity constraints to enforce semantics. One type of constraints is XML functional dependency (XFD). When a source schema is transformed to a target schema, XFDs can also be transformed. Thus, the problem how schema and data transformation should cause XFD transformation becomes important. In this paper, we study the transformation of XFDs. Towards this problem, we first define the XFDs over the XML document type definition (DTD) and the satisfactions of XFDs. We then show how XFDs are transformed and whether XFDs are valid when the DTDs are transformed. We further investigate whether the transformed XFDs are preserved by the transformed data.